Formulation and Characterization of Plant Essential Oil Based Nanoemulsion: Evaluation of its Larvicidal Activity Against Aedes aegypti - Ghosh, Vijayalakshmi; Mukherjee, Amitava; Ch, N. (Asian Journal of Chemistry, 2013)
Attraction of nanoemulsion is due to their potential advantages over conventional emulsions which owes to their unique physicochemical properties such as very small droplet size, optical transparency and long term physical stability. In this study, O/W nanoemulsion was formulated from plant essential oil and non-ionic surfactant Tween 20 by ultrasonic emulsification method. Transparent nanoemulsion with mean droplet diameter of 30 nm was obtained at 1:3 ratio (v/v) of oil and surfactant and was found to be stable. There was no change in droplet diameter even after storage for 1 month. Surfactant concentration played a vital role in physical appearance, droplet size, viscosity, turbidity and stability of emulsion. Physicochemical characterization (hydrodynamic diameter, pH, conductivity and viscosity) and larvicidal activity against Aedes aegypti have been studied. The nanoemulsion demonstrated time and dose dependent larvicidal activity. The results suggested that formulated nanoemulsion can be used for control of mosquito vector-borne diseases.